A Feminist Rhetorical Analysis of Anti-feminist Poetry in English and Arabic - Ali, Hatim F.; Al-Utbi, Mahdi I. (Al-Adab Journal, 2021)
Language is the fundamental element of communication and understanding in society. It relates immediately to human thoughts and is embodied in written or spoken signs or signals. The field that scientifically studies language (its forms and structures) is called Linguistics. Among the linguistic studies of language is Rhetoric which studies the importance of speech or texts for the audience. Rhetoric is the art of persuasion; it comprises different arguments raised by the speaker/writer depending on social, religious, moral or even traditional evidence in order to prove that the raised arguments are real. In this way, the writer/speaker associates the language to similar or related realities in order to reach the purpose of her/his language. However, presenting arguments and evidence it not always accurate because there are arguments that rely on weak evidence. The purpose of argumentative techniques is still to persuade the audience about a personal view or a societal concept. From this perspective, the feminist linguists suggest that rhetoric is actually masculine; that is, rhetoric is anti-feminist. Therefore, linguists presented a great deal of evidence to prove this theory and bring the feminist ideology into rhetoric. This study aims at providing a feminist rhetorical analysis of the anti-feminist poetry to study the status of women in rhetoric and whether the arguments that demean women are true or not. For this purpose, the current study utilizes Fiorenza’s (1995) model of analysis; a feminist rhetorical tool to analyze anti-feminist poems written by male poets in English and Arabic in order to study the arguments as well as the evidence the poets present against women.